1999
DOI: 10.1074/jbc.274.33.22903
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic Acid Oxygenation by COX-1 and COX-2

Abstract: Prostaglandins were discovered in human semen in 1930, but their low concentrations and instability precluded identification for nearly 30 years (for a brief historical review, see Ref. 1). Once they were identified, it was clear they arose from polyunsaturated fatty acids by a complex series of reactions involving oxygenation, cyclization, and the generation of five chiral centers from an achiral substrate. The mechanism of prostaglandin biosynthesis was outlined in 1967 by Hamberg and Samuelsson (2), and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
285
1
6

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 480 publications
(298 citation statements)
references
References 58 publications
4
285
1
6
Order By: Relevance
“…The production of pro-inflammatory prostanoids is an injurious mechanism associated to the COX-2 enzymatic activity and this process is associated with the generation of highly reactive oxygen species, which have potent deleterious effects on cells [42]. We found that delayed treatment of rats with nimesulide completely abolished the marked increase in PGE 2 seen in the ischemic cortex 24 h after stroke.…”
Section: Discussionmentioning
confidence: 67%
“…The production of pro-inflammatory prostanoids is an injurious mechanism associated to the COX-2 enzymatic activity and this process is associated with the generation of highly reactive oxygen species, which have potent deleterious effects on cells [42]. We found that delayed treatment of rats with nimesulide completely abolished the marked increase in PGE 2 seen in the ischemic cortex 24 h after stroke.…”
Section: Discussionmentioning
confidence: 67%
“…10,[24][25][26] This review will focus on the structural and functional basis of the inhibition of COX enzymes by nonselective and COX-2 selective inhibitors. It will integrate kinetic, mechanistic, and structural information to illustrate not only the range of molecules with COX inhibitory activity but also the diversity of mechanisms by which they act.…”
Section: Introductionmentioning
confidence: 99%
“…process, phospholipase A 2 catalyzes the release of arachidonic acid from membrane phospholipids, while COX catalyzes the conversion of arachidonic acid into PGs (2,3). There are two isoforms of COX, COX-1 and COX-2, the product of two different genes.…”
mentioning
confidence: 99%